Figur Moral Dalam Politik Papua: Strategi Komunikasi Benhur Tomi Mano (BTM) Pasca Kekalahan Elektoral 2025 - Rani Yanti Ngabalin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the political communication strategy of Dr. Drs Benhur Tomi Mano, M.M (BTM) following his electoral defeat in the 2025 Papua Repeat Election (PSU), highlighting his transformation from an electoral leader to a moral leader. Employing a descriptive qualitative approach, this research uses discourse analysis, cultural semiotics, and media triangulation to explore BTM’s narratives, symbols, and political messages within Papua’s socio-cultural context. The findings reveal that BTM transformed electoral loss into symbolic and moral capital through value-based communication rooted in local wisdom, spirituality, and social solidarity. His rhetoric of compassion, defense of indigenous land (Cycloop), and continuous presence among communities strengthened his moral legitimacy beyond formal authority. The study concludes that BTM’s communication strategy represents a model of Papuan leadership that frames politics as a domain of service, reconciliation, and social healing.